IMPACT OF ONLINE AND OFFLINE ACCOUNTING EDUCATION IN KERALA - Idicula, Ebby Joseph; Rajesh K P; Francis, Tina Bloosom (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The role of accounting is crucial across various industries. Therefore, it is important to incorporate it into the educational framework. The introduction of the New Education Policy and advancements in technology have led to significant transformations in the education sector. These alterations have also impacted accounting education within the field. A research study was conducted among 578 commerce students in Kerala to evaluate the effectiveness of online versus offline accounting education. The analysis of the data revealed that while online accounting education is a valuable resource, it cannot fully replace traditional classroom learning in accounting education.